Real-world retrospective comparison of 0.19 mg fluocinolone acetonide and 0.7 mg dexamethasone intravitreal implants for the treatment of diabetic macular edema in vitrectomized eyes - Coelho J (Dove Medical Press, 2019)
João Coelho1, Luísa Malheiro1, João Melo Beirão1,2, Angelina Meireles1,2, Bernardete Pessoa1,2 1Unit of Ophthalmology, Centro Hospitalar Universitário Do Porto, Porto, Portugal; 2Unit of Ophthalmology, Universidade Do Porto-Instituto Ciências Biomédicas Abel Salazar, Porto, PortugalCorrespondence: João CoelhoUnit of Ophthalmology, Centro Hospitalar Universitário do Porto, Largo Prof. Abel Salazar, Porto 4099-001, PortugalTel +351 91 765 6826Email joaomsmc@gmail.comPurpose: The aim of this study was to evaluate the long-term real-world effectiveness of FAc and DEX implants in vitrectomized DME eyes in a real-world setting.Methods: This was a non-interventional, retrospective, comparative study of 46 vitrectomized eyes in 33 patients with persistent or recurrent DME quantified best-corrected visual acuity (BCVA), central foveal thickness (CFT) and intraocular pressure (IOP) over up to 37 months.Results: Both FAc and DEX treatment led to statistically and clinically significant improvements in BCVA and CFT. FAc >10-letter improvement on the Early Treatment Diabetic Retinopathy Study [ETDRS] chart over months 3–24 and a sustained ∼200 μm CFT reduction over months 1–24; DEX: >5-letter improvement on the ETDRS chart at months 1 and 3 and >100 μm CFT reduction at month 1. FAc demonstrated sustained, stable and predictable effects on BCVA and CFT over 24 months and also improved BCVA and decreased CFT in a cohort of DME eyes that was refractory to DEX over 6 months.Conclusion: This real-world study demonstrates long-term effectiveness of FAc in vitrectomized DME eyes and sustained effectiveness in DME eyes that did not respond to DEX therapy.Keywords: diabetic macular edema, fluocinolone acetonide, dexamethasone implant, intravitreal implants, real-world, vitrectomy